Redetermination of the crystal structure of tetrakis(4-chlorobenzyl)tin(IV), C28H24Cl4Sn - Lee, See Mun *; Lo, Kong Mun *; Tiekink, Edward R. T. * (de Gruyter, 2019)
[C28H24Cl4Sn], orthorhombic, Fdd2 (no. 43), a = 22.01600(10) Å, b = 20.79690(10) Å, c = 11.15230(10) Å, V = 5106.24(6) Å3, Z = 8, Rgt(F) = 0.0134, wRref(F2) = 0.0370, T = 100(2) K. CCDC no.: 1903633 The molecular structure is shown in the figure. Table 1 contains crystallographic data and Table 2 contains the list of the atoms including atomic coordinates and displacement parameters.